The Effect Of Earning Per Share And Debt To Equity Ratio On Stock Price With Independent Commissioners As Moderation Variable (Study On Infrastructures Sector Companies Listed On The IDX Period 2018-2021) - HALIM, Maria Monica Angela; SAERANG, David Paul Elia; KOROMPIS, Claudia Wanda Melati (PT Keberlanjutan Strategis Indonesia, 2022)
The stock price is a reflection of the value of a company. The higher the stock price, the higher the value of the company. The company's share price is very important for various parties. The better the information provided by the company's management, the better the signals received by investors, resulting in the company's share price will increase in line with the Signaling Theory. This study aims to determine the effect of Earning Per Share and Debt to Equity Ratio on share prices with Independent Commissioners as moderation variables in infrastructure sector companies listed on the Indonesia Stock Exchange. The sample used was an infrastructure sector company listed on the Indonesia Stock Exchange for the 2018-2021 period that met the predetermined criteria, namely 47 samples. The data source used is quantitative data. The analysis techniques used include descriptive statistical analysis, outer models, inner models and hypothesis testing with the help of the SmartPLS 3.0 program. the results showed that Earnings per share and Debt to equity ratio influenced stock prices and independent commissioners did not moderate the effect of Earning Per Share and Debt to Equity Ratio on Stock Prices.